Luxembourg : Staff Report for the 2015 Article IV Consultation. - International Monetary Fund. European Dept. (Washington, D.C. : International Monetary Fund, 2015)
This 2015 Article IV Consultation highlights that Luxembourg's economic model, emphasizing fiscal stability, openness, firm prudential oversight, and responsiveness to investor needs, is delivering strong growth. Buoyant financial services exports contributed to real growth of close to 3 percent in 2014, with strong job creation. Budget 2015 launched a multi-year fiscal consolidation aimed at offsetting falling revenues from electronic commerce. The economy faces important challenges going forward. Evolving international tax transparency standards, in which Luxembourg is participating fully, could impact the revenue base. Growth is projected at 2.5 percent in 2015.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet